Development and Optimization of Nanolipid-Based Formulation of Diclofenac Sodium: In Vitro Characterization and Preclinical Evaluation - Ameeduzzafar Zafar; Nabil K Alruwaili; Syed Sarim Imam; Mohd Yasir; Omar Awad Alsaidan; Ali Alquraini; Alenazy Rawaf; Bader Alsuwayt; Md. Khalid Anwer; Sultan Alshehri; Mohammed M. Ghoneim (MDPI AG, 2022)
In the present research study, we formulate bilosomes (BMs) of diclofenac (DC) for oral delivery for enhancement of therapeutic efficacy (anti-inflammatory disease). The BMS were prepared by thin film hydration method and optimized by Box-Behnken design (BBD) using cholesterol (A), lipid (B), surfactant (C), and bile salt (D) as formulation factors. Their effects were evaluated on vesicle size (Y1) and entrapment efficacy (Y2). The optimized DC-BMs-opt showed a vesicle size of 270.21 ± 3.76 nm, PDI of 0.265 ± 0.03, and entrapment efficiency of 79.01 ± 2.54%. DSC study result revealed that DC-BMs-opt exhibited complete entrapment of DC in BM matrix. It also depicted significant enhancement (p < 0.05) in release (91.82 ± 4.65%) as compared to pure DC (36.32 ± 4.23%) and DC-liposomes (74.54 ± 4.76%). A higher apparent permeability coefficient (2.08 × 10−3 cm/s) was also achieved compared to pure DC (6.6 × 10−4 cm/s) and DC-liposomes (1.33 × 10−3 cm/s). A 5.21-fold and 1.43-fold enhancement in relative bioavailability was found relative to pure DC and DC liposomes (DC-LP). The anti-inflammatory activity result showed a significant (p < 0.05) reduction of paw edema swelling compared to pure DC and DC-LP. Our findings revealed that encapsulation of DC in BMs matrix is a good alternative for improvement of therapeutic efficacy.